DEVONIAN STAGE BOUNDARIES OF THE URALS - Sapel'nikov V.P.; Nasedkina V.A.; Mizens L.I.; Zenkova G.G. (My University, 2001)
In the Urals the Devonian is represented by shelf and continental slope facies, as well as various volcanogenic rocks. Palaeontological data, including conodonts and brachiopods, are of use in regional correlation, although most of the stage boundaries are not yet precisely determined in the area.
Keywords: Devonian; Urals; conodonts; brachiopods; Paleozoic::Devonian; Палеозой::Девонская